2017
DOI: 10.1002/lary.27021
|View full text |Cite
|
Sign up to set email alerts
|

Does the diameter of the stapes prosthesis really matter? A prospective clinical study

Abstract: 2b Laryngoscope, 1922-1926, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
0
8
0
1
Order By: Relevance
“…On the contrary, a meta-analysis by Laske et al 11 reported that a 0.6-mm piston is associated with significantly better post-operative ABG at low and mid frequencies, compared to a 0.4 mm prosthesis. Bernardeschi et al 28 demonstrated a significant difference in AC gain, AC threshold at 0.125 and 0.25 kHz and BC threshold at 0.25 kHz in favour of the 0.6-mm group. The latter study is one of the few to be designed as a prospective one, on consecutive cohorts, with minimum risk of bias.…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, a meta-analysis by Laske et al 11 reported that a 0.6-mm piston is associated with significantly better post-operative ABG at low and mid frequencies, compared to a 0.4 mm prosthesis. Bernardeschi et al 28 demonstrated a significant difference in AC gain, AC threshold at 0.125 and 0.25 kHz and BC threshold at 0.25 kHz in favour of the 0.6-mm group. The latter study is one of the few to be designed as a prospective one, on consecutive cohorts, with minimum risk of bias.…”
Section: Discussionmentioning
confidence: 95%
“…The comparison among pistons of different diameters is a matter of great interest [Quaranta et al, 2019]; however, in our study, the low sample numbers obtained in the subgroups do not allow the achievement of significantly different results. A clear evidence that a 0.6-mm-diameter prosthesis gives better audiological results than 0.4 in larger cohorts has been proven [Laske et al, 2011; Bernardeschi et al, 2018], and it would be interesting to ascertain if this remains stable over time on larger cohorts. A debated topic concerns the natural evolution of the unoperated otosclerotic ear.…”
Section: Discussionmentioning
confidence: 99%
“…Die Verwendung von Prothesen mit einem Pistondurchmesser von 0,4 oder 0,6 mm wird kontrovers diskutiert [41]. Während ein dünnerer Piston aus anatomisch-chirurgischer Sicht Vorteile zu bieten scheint, gibt es zunehmende Hinweise auf einen audiologischen Vorteil, insbesondere bei den tieferen Frequenzen, bei einem Pistondurchmesser von 0,6 mm [3], [21], was auch vereinbar ist mit den kolbenförmigen Schwingungen des Stapes im tieferen Frequenzbereich (siehe Teil 1 dieses Beitrags [25]).…”
Section: Pistondurchmesserunclassified